2022
DOI: 10.3389/fpsyg.2022.909414
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Reflective Functioning as a Predictor of Substance-Using Mothers' Treatment Outcome: Comparing Results From Two Different RF Measures

Abstract: Mothers with prenatal substance use disorder (SUD) often show broad deficits in their reflective functioning (RF), implying severe risk for the relationship with their baby. Two different types of prenatal maternal RF may be important for parenting: adult attachment-focused-RF (AAI-RF), regarding parent's own childhood experiences, and parenting-focused RF (PRF) regarding their own current process of becoming a parent. However, their inter-relations and potentially different roles for parenting intervention ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 86 publications
0
3
0
Order By: Relevance
“…Again, using the same sample, mothers with SUD were lower on each of the EA dimensions, as compared to non-using mothers with obstetric risk. Using the same sample, Flykt et al (2022) and Isosävi et al (2016) found that neither maternal attachment nor her reflective functioning, both measured with AAI prenatally, predicted mother-infant interaction quality at 4 months. However, reflective functioning measured with AAI was predictive of improvements in EA following the intervention (4 and 12 months) and most clearly in the negative interactions picked up by the nonintrusiveness and nonhostility scales.…”
Section: Ea In Early High-risk Contextsmentioning
confidence: 94%
See 1 more Smart Citation
“…Again, using the same sample, mothers with SUD were lower on each of the EA dimensions, as compared to non-using mothers with obstetric risk. Using the same sample, Flykt et al (2022) and Isosävi et al (2016) found that neither maternal attachment nor her reflective functioning, both measured with AAI prenatally, predicted mother-infant interaction quality at 4 months. However, reflective functioning measured with AAI was predictive of improvements in EA following the intervention (4 and 12 months) and most clearly in the negative interactions picked up by the nonintrusiveness and nonhostility scales.…”
Section: Ea In Early High-risk Contextsmentioning
confidence: 94%
“…Otherwise, there was no link with any of the EA dimensions in either the group of autonomous substance abusing mothers or those who were autonomous nonusing but at obstetric risk, which may raise the question of how "autonomous" and "substance abusing" may be quite different than "autonomous" in a normative sample. Based on Flykt et al (2022) study, it may also be that acute substance use problems (as prenatal measure was conducted pre-treatment, when many of the mothers were just in the process of trying to give up substances) may hinder the usual links between AAI and EA, although they might become visible later. It is possible that more research is needed on the AAI-EA link in high-risk samples, as the meaning of "autonomous" and the meaning of "emotionally available" may be quite different in one or both evaluation systems.…”
Section: Ea In Early High-risk Contextsmentioning
confidence: 99%
“…A growing body of research supports these proposals. For instance, higher parental mentalising has been prospectively linked to higher maternal sensitivity (Ensink et al, 2019;Farrow & Blissett, 2014;Flykt et al, 2022), and randomised controlled or clinical trials indicate that interventions targeting parental mentalising can increase maternal sensitivity (e.g., Salo et al, 2019;Suchman et al, 2017Suchman et al, , 2018 and reduce parenting stress (Adkins et al, 2022;Sieverson et al, 2021). With regard to child development, prospective studies have found that higher parental mentalising fosters secure child attachment (e.g., Ensink et al, 2019;Gagné et al, 2021;Meins et al, 2012), and meta-analytic findings indicate that these effects are both direct and indirect (i.e., via sensitivity; Zeegers et al, 2017).…”
Section: The Importance Of Parental Mentalising For Caregiving and Ch...mentioning
confidence: 99%